1982
DOI: 10.1111/j.1365-2265.1982.tb01611.x
|View full text |Cite
|
Sign up to set email alerts
|

Pubertal Maturation of the Lh Stimulatory Response to Clomiphene Citrate in Congenital Virilizing Adrenal Hyperplasia*

Abstract: To determine the LH release response to clomiphene citrate in children with virilizing congenital adrenal hyperplasia (CAH), we examined six patients with glucocorticoid-treated virilizing CAH, five girls and one boy, chonological age (CA) 4 years 2 months-15 years 9 months and bone age (BA) range 8-18 years. All the patients but one, were treated with nocturnal dexamethasone. Their ages at the onset of treatment ranged from 2 years 6 months to 13 years 8 months. An additional boy (CA = 4 years 3 months and BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…At low doses (25-50 mg/day), clomiphene is reportedly ineffective in prepubertal boys, but stimulates gonadotropin secretion in pubertal and adult males. At high doses (500 mg/day), clomiphene suppresses gonadotropin secretion even in normal adult males (25,26). In our study, a relatively low dose of clomiphene (50 mg/day) was able to increase and sustain serum gonadotropins and testosterone levels even in face of raising estradiol levels, which indicates an anti-estrogenic effect at the hypothalamus and/or pituitary.…”
Section: Discussionmentioning
confidence: 63%
“…At low doses (25-50 mg/day), clomiphene is reportedly ineffective in prepubertal boys, but stimulates gonadotropin secretion in pubertal and adult males. At high doses (500 mg/day), clomiphene suppresses gonadotropin secretion even in normal adult males (25,26). In our study, a relatively low dose of clomiphene (50 mg/day) was able to increase and sustain serum gonadotropins and testosterone levels even in face of raising estradiol levels, which indicates an anti-estrogenic effect at the hypothalamus and/or pituitary.…”
Section: Discussionmentioning
confidence: 63%
“…There is a demonstrable change from their unaltered or negative response to a positive one when the bone age is around 8-9 years. This pattern of LH release during the clomiphene citrate test is similar to those observed in normal children (Kulin el al., 1971(Kulin el al., , 1972Nankin et af., 1971) and late treated virilizing congenital adrenal hyperplasia (Moreira et al, 1982) in which a change in the prepubertal LH release is observed in mid to late puberty, when the bone age is around 13-14 years. Since clomiphene citrate may act predominantly as an anti-oestrogen at the hypothalamic level (Adashi, 1984), our data indicate that the activation of the hypothalamic pubertal mechanism in CPP usually progresses in a sequence similar to that described for normal puberty, but occurs at a much earlier age.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the LH response to clomiphene citrate increases in the late pubertal stages of normal children (Kulin etal., 1971(Kulin etal., ,1972Nankinetal., 1971)whobecomecapableof responding in an adult fashion, probably reflecting the maturation of the hypothalamic pubertal mechanism. We have previously documented the LH responses to clomiphene citrate in children with combined precocious puberty due to late treatment of congenital adrenal hyperplasia (Moreira et al, 1982). This study indicated that secondary precocious hypothalamic maturation may occur in response to one of the forms of peripheral precocious puberty.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…In the hypothalamus-pituitary axis, at low doses (25 to 50 mg/day), clomiphene is reportedly ineffective in prepubertal boys, but stimulates gonadotropin secretion in pubertal and adult males. At high doses (500 mg/day), clomiphene suppresses gonadotropin secretion even in normal adult males (22,23).…”
Section: Discussionmentioning
confidence: 99%